IDENTIFIKASI BAKTERI Escherichia coli, Shigella sp. DAN Staphylococcus aureus SEBAGAI BIOMARKER CEMARAN PADA SUMBER AIR DAERAH STUNTING DI KELURAHAN BELAWAN SICANANG, KECAMATAN MEDAN BELAWAN, MEDAN - Tania Regita Sari; Dinda Aulia Habib; Febri Sembiring; Gabriella Septiani Nasution; Lestari Rahmah (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Stunting is a disorder of growth and development of children due to chronic malnutrition and repeated infections, which are characterized by below standard height. Water is a kind of resource which required for community household activities,. Therefore, water, sanitation and hygiene become particular concern. Contamination by Enterotoxigenic Escherichia coli that transmitted through water can increase the risk of stunting in children with continuous diarrhea. This research was conducted to identify biomarkers in water sources for local residents with stunting in Belawan Sicanang Village, Medan. The biomarkers used were E. coli, Shigella sp., and Staphylococcus aureus. The method used in this study is the Most Probable Number (MPN) and Total Plate Count (TPC). The results of this study indicated that 2 out of 3 drinking water samples were contaminated with E. coli., and 3 out of 3 clean water samples were contaminated with E. coli. Meanwhile, the other two biomarkers were not detected in all types of samples.